The Relationship of Transformational Leadership Behavior of School Principles and Teacher Achievement Motivation with Learning Quality - Ansar Ansar; Warni Tune Sumar; Feliya Tanaiyo (Green Publisher Indonesia, 2022)
This study aims to determine: the relationship between the principal's transformational leadership behavior and the quality of learning in SMPNs in Kota Selatan Subdistrict, Gorontalo City, the relationship between teacher achievement motivation and learning quality in SMPNs in Kota Selatan Subdistrict, Gorontalo City, the relationship between principals' transformational leadership behavior and teacher achievement motivation with the quality of learning at SMPN in Kota Selatan District, Gorontalo City. The sample calculation is 10% of the population of 174 so the sample used in this study is 64 employees. This study uses a quantitative correlation type approach. The results: 1) In testing the significance of the correlation coefficient, it turns out that the value of tcount is greater than t-list (t-count > t-list = 2.729 > 1.999) or the price of t-count is outside the acceptance of H0. So it can be concluded that the correlation above is really significant. 2) In testing the significance of the correlation coefficient, it turns out that the price of tcount is greater than tList (tcount > tList = 5.587 < 1.999) or the price of t-count is outside acceptance. 3) Principal transformational leadership behavior and teacher achievement motivation have a close relationship with learning quality. Seen from the results of the test significance test that the calculated F value is 15.7678. Thus, the hypothesis which states that there is a